Variations in Root System Architecture Responses to Meloidogyne enterolobii and Meloidogyne incognita Parasitism in Sweetpotato Genotypes - David Galo; Arthur Villordon; Tristan T. Watson (HortScience)
In sweetpotato (Ipomoea batatas), the emergence and development of lateral roots (LRs) is crucial for determining the root system architecture (RSA), which impacts plant establishment, storage root formation, and yield potential. This study evaluated RSA responses of five sweetpotato genotypes to Meloidogyne enterolobii or Meloidogyne incognita infection. The genotypes included ‘Beauregard’ (susceptible to both nematodes), ‘Jewel’ (resistant to M. enterolobii and moderately resistant to M. incognita), and Louisiana State University Agricultural Center genotypes LA14-31 (resistant to M. enterolobii and moderately resistant to M. incognita), LA18-100 (susceptible to M. enterolobii and resistant to M. incognita), and LA19-65 (resistant to M. enterolobii and susceptible to M. incognita). Sweetpotato vine cuttings were inoculated at planting with approximately 3000, 500, or no eggs of either nematode species. Entire root systems were collected at 14 and 21 days postinoculation (DPI) and scanned. Images were analyzed using RhizoVision Explorer software. Gall counts per root system and RSA attributes such as lateral root length, surface area, and volume were evaluated. Variations in gall formation and RSA attributes among genotypes were observed as early as 14 DPI and continued at 21 DPI, with LA18-100 (released as ‘Avoyelles’) showing consistently greater lateral root length, surface area, and volume compared with those of the other genotypes. The RSA response to varying nematode inoculum densities was genotype-specific and not linked to the resistance response to M. enterolobii or M. incognita. The incorporation of RSA attributes into sweetpotato breeding programs has potential for identifying genotypes with favorable rooting characteristics.